Variabilidad físicoquímica del agua durante el proceso productivo del camarón patiblanco (litopenaeus vannamei), en una laguna camaronera, sitio El Pueblito, Chone - Cedeño Muñoz, Jonathan Javier (2019)
The present investigation had the purpose of evaluating the physicochemical variability of the water during the production process of the white-legged shrimp (Litopenaeus vannamei), in a shrimp lagoon located in El Pueblito, Chone canton, for which the change in the physicochemical characteristics of the used water was determined in the production process of the shrimp farm, through monitoring the effluent during the production process. The parameters analyzed in this investigation were the hydrogen potential (pH), temperature, dissolved oxygen (DO), total dissolved solids (TDS), biochemical oxygen demand (BOD5), chemical oxygen demand (COD), nitrites (NO2) and nitrates (NO3). At the pH the tributary was 7.35 and the effluent was 9.15; the temperature was 28 ºC in the tributary and 25.4 ºC in the effluent; the TDS in tributary was 0.34 mg/l and in the effluent 0.99 mg/l; the COD in the tributary was 0.9 mg/l and in the effluent 1140 mg/l; in BOD5 the tributary was 2 mg/l and the effluent was 25 mg/l; the nitrites were 0.045 mg/l to the effluent and 0.08 mg/l in the effluent; the nitrates in the tributary were 0.06 mg/l and in the effluent 0.09 mg/l; the OD in the tributary was 3.5 mg/l and in the effluent of 5 mg/l, showing that there is variability in the water used in the system. The effluent was compared with the current environmental norm of Ecuador stated in book VI, of Annex 1, table 9 of the TULSMA, "Limits of discharge to a body of fresh water", in which the parameters that did not comply with the standard were the COD exceeding the permissible limit (COD> 250 mg/l) with 850 mg/l and the pH above the current environ